Interaction Between High Pressure Releases from Small Holes and the Ground Surface - Alessandro Pinciroli; Renato Rota; Valentina Busini (Chemical Engineering Transactions)
High-pressure releases are a significant concern in industrial safety, particularly when they involve flammable gases, as these can have severe consequences for both workers and the environment. Common flammable compounds include methane, propane, and hydrogen — the latter being a relatively recent energy carrier gaining traction in various applications. High-pressure releases are notable for their high momentum, which can extend the flammable cloud over considerable distances and potentially cause damage to vulnerable structures. One well-known fluid behavior is the Coanda effect, which occurs near flat surfaces such as the ground. In the event of a high-pressure release, this effect can further expand the flammable area. Previous studies have explored the influence of the ground on the extension of high-pressure jets from large orifices. This work aims to investigate releases from small orifices to understand their behavior near the ground and determine whether they can be treated similarly to larger releases. Further investigation is also focused on determining whether the low release height allows the jet to hit the ground due to its natural opening angle and the possible incidence of this phenomenon in relation to the Coanda effect.